2015
DOI: 10.1109/jssc.2015.2413841
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Aware Program-and-Read Schemes for 3D Stackable Vertical-Gate BE-SONOS NAND Flash Against Cross-Layer Process Variations

Abstract: 3D vertical-gate (3DVG) NAND flash is a promising candidate for next-generation high-density nonvolatile memory. Cross-layer process variation renders 3DVG NAND susceptible to decreased speeds, yield, and reliability. This can be attributed to (a) cross-layer mismatch in bitline capacitance ( ), (b) the need for long program cycles, and (c) sensing-margin (SM) loss induced by the effects of background-pattern-dependency (BPD). This study proposes three circuit-level techniques to overcome these issues by emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Among the three axes, we expect the variation along the z-axis (i.e., layer-to-layer variation) to be the most significant, due to the new challenge of stacking multiple flash cells across layers. Prior work has shown that current circuit etching technologies are unable to produce identical 3D NAND cells when punching through multiple stacked layers, leading to significant variation in the error characteristics of flash cells that reside in different layers [38,92].…”
Section: Layer-to-layer Process Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three axes, we expect the variation along the z-axis (i.e., layer-to-layer variation) to be the most significant, due to the new challenge of stacking multiple flash cells across layers. Prior work has shown that current circuit etching technologies are unable to produce identical 3D NAND cells when punching through multiple stacked layers, leading to significant variation in the error characteristics of flash cells that reside in different layers [38,92].…”
Section: Layer-to-layer Process Variationmentioning
confidence: 99%
“…Prior work proposes circuit-level and systemlevel techniques to tolerate layer-to-layer process variation in 3D NAND flash memory. Two recent works propose to use different read reference voltages for different layers [38,96], which is similar to the LaVAR technique that we propose in Section 6.1. Unlike our work, these prior works do not (1) design a detailed mechanism like LaVAR to learn and use the V opt in a lookup table, or (2) evaluate their techniques using real characterization data.…”
Section: Related Workmentioning
confidence: 99%
“…A split-gate architecture was also proposed in order to relax the lithography on the select gates (split-gate architecture). Several other innovations have led to a very compact layout of the VG NAND and its operation [29][30][31][32].…”
Section: Single-gate Vertical Channel (Sgvc) Architecturementioning
confidence: 99%
“…It must be noted here that the overall performance of the 3D NAND architectures should be finally evaluated after a proper system implementation. In fact, several drawbacks of an architecture can be corrected or mitigated by implementing ad hoc program algorithms and ECC [4,17,31,32,[34][35][36][37].…”
Section: Comparison Between Ct Flat Cell and Gaa Cell Structuresmentioning
confidence: 99%
“…The layers with the higher operating point will result in higher background pattern dependency. In order to level this kind of dependency, a method was proposed where each bitline is pre-charged to specific layer-dependent voltage instead of discharging all the bitlines to GND during the setup phase [31].…”
Section: Read Operationmentioning
confidence: 99%